2021
DOI: 10.1111/anu.13355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin E on growth performance, antioxidant capacity and lipid metabolism of juvenile golden pompano Trachinotus ovatus

Abstract: Vitamin E (VE), consisting of tocopherols, tocotrienols and the derivatives, serves as a lipid-soluble antioxidant providing nutrients to animals including fish (Bramley et al., 2000). Its primary function is to act as a free radical scavenger that protects cells and tissues against the deleterious effects of free radicals (Liu et al., 2018;Naderi et al., 2019;Wang et al., 2019). Besides, VE can increase antioxidant ability of fish by enhancing the antioxidant enzyme activities containing superoxide dismutase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…golden pompano [37], and blunt bream (Megalobrama ambycephala) [38], appropriate VE supplementation was found to have a growth-promoting effect, although high doses of VE did not further increase fish growth. Previous studies have shown that 50-100 mg/kg VE can meet the growth demands for Nile tilapia at a dietary lipid level of 50 g/kg [18].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…golden pompano [37], and blunt bream (Megalobrama ambycephala) [38], appropriate VE supplementation was found to have a growth-promoting effect, although high doses of VE did not further increase fish growth. Previous studies have shown that 50-100 mg/kg VE can meet the growth demands for Nile tilapia at a dietary lipid level of 50 g/kg [18].…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, the dietary VE level did not significantly affect the growth performance of female tilapia. In studies on spotted seabass ( Lateolabrax macroatus ) [ 36 ], golden pompano [ 37 ], and blunt snout bream ( Megalobrama ambycephala ) [ 38 ], appropriate VE supplementation was found to have a growth-promoting effect, although high doses of VE did not further increase fish growth. Previous studies have shown that 50–100 mg/kg VE can meet the growth demands for Nile tilapia at a dietary lipid level of 50 g/kg [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, vitamins contribute to the development of the immune system, while also helping in the digestion of other nutrients [ 81 , 82 ]. The fat-soluble vitamins (α and γ tocopherols) are good natural antioxidants that impede lipid oxidation in biological systems by stabilizing hydroperoxyl and in mopping out other free radicals [ 83 , 84 , 85 ]. As vitamins cannot be synthesized de novo by animals, they must be supplied constantly by food, thus incorporation of the studied insects in diets would likely serve as an alternative source of vitamins.…”
Section: Resultsmentioning
confidence: 99%
“…Organophosphate (OP) compounds are most commonly used insecticides which non-competitively inhibit the enzymatic activity of acetylcholine esterase which metabolizes acetylcholine. The enhanced cholinergic activity of muscarinic and nicotinic acetylcholine receptors causes the acute symptoms of OP poisoning (Zhang et al, 2021;Yongcai et al, 2020 andMinton andMurray, 1988). Pyrethroids are ion channel poisons that prolong neuronal excitement without being cytotoxic.…”
Section: Introductionmentioning
confidence: 99%